PENGENDALIAN Ganoderma boninense OLEH Trichoderma sp. SBJ8 PADA KECAMBAH DAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI TANAH GAMBUT - Rizky Alviodinasyari; Atria Martina; Wahyu Lestari (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Basal stem rot disease caused by Ganoderma boninense is the most destructive disease in oil palm plantation in Indonesia, especially in the peatland. The use of chemical pesticides as controlling agent is hazardous to environment and human health. The alternative to control this disease is by using biological agent Trichoderma sp. SBJ8 in the form of Ganofend biofungicide. The research were aimed to study the effectivity ofTrichoderma sp. SBJ8 isolate in suppressing in vitro growth of G. boninense, as well as to determine the ability of Ganofend biofungicide in inhibiting the growth of G. boninense on the oil palm germination and seedling. The experimental study included two cultures i.e. in vitro and in vivo using randomized design with 6 treatments: without Ganofend biofungicide treatment, 100 g Ganofend biofungicide treatment, and with immersing in Ganofend biofungicide solution for both root and seedling of oil palm. The results showed that the isolates of Trichoderma sp. SBJ8 could inhibit the growth of G. boninense in 4th day up to 65,25%. The treatment using Ganofend biofungicide was effective to decrease the mortality percentage of oil palm germination and not causes seedling death.